Freaky tales [videorecording (Blu-Ray + DVD)] - Fleck, Ryan, 1976-; Boden, Anna; Pascal, Pedro; Hanks, Tom; Ellis, Jay, 1981- (Lionsgate, 2025)
An NBA star, a corrupt cop, a female rap duo, teenage punks, neo-Nazis and a debt collector embark on a collision course in 1987 Oakland, Calif.